Alasan Amerika Serikat Menyalurkan Kontribusi Dana Multilateral Untuk Sudan Selatan Melalui WFP (World Food Programme) Tahun 2014-2017 - Pavilia, Novellita; Priadarsini, Ni Wayan Rainy; Kumala Dewi, Putu Ratih (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT Foreign aid is one example of an issue that often appears in a study of International Relations. Countries like the United States often use foreign aid to respond some issues like conflict which is happening in South Sudan.The United States has supported those country since the beginning of its independence and when the civil war struck again in mid-December 2013, those country committed to continue its support through the provision of foreign aid. On one side, congress then questioned about the circumstances of South Sudan whose has not shown any progress yet. Some member of congress has suggested that the United States should prioritize the humanitarian aid to helping South Sudan society, one of the example is could be through the international institutions such as WFP. This study aims to see the reason of United States channels its multilateral funding contribution for South Sudan through WFP (World Food Programme). Keywords: State, United States, World Food Programme (WFP), Foreign Aid, South Sudan, Civil War, Multilateral Contribution